Inflation in the Indian Economy - Moni, D. M. (Asian Journal of Managerial Science, 2014)
Inflation is one of the most retarding factors of economic life and economic development. In fact, it affects almost all economic activities as well as consumption pattern of average and poor people. Since 1947, prices have continuously risen in India. It is seen that fluctuations in prices create an atmosphere of uncertainty which is not conducive to the developmental activities. In other words inflation creates uncertainty in development activities which cause a decline in the purchasing power of money. At the same time, stability in the price level is conducive for economic stability. It is quite interesting to note that what India experiences in instability in the price level are different from Keynesian view who stated that inflation occurs after the achievement of full employment level. But it is not so in India where increase in government expenditure is the major cause to inflation. Hence, the investigators attempt to analyze the inflationary trend and growth of public expenditure in India over a period of time. The fluctuation in price level is measured in terms of wholesale price index or consumer price index.